The Participation of Trans Women in Competitive Fencing and Implications on Fairness: A Physiological Perspective Narrative Review - Victoria Tidmas; Clare Halsted; Mary Cohen; Lindsay Bottoms (MDPI AG, 2023)
Debate has surrounded whether the participation of trans women in female sporting categories is fair, specifically the retained male physiological advantage due to increased testosterone compared to cisgender females. Recently, individual sporting organisations have been investigating and assessing policies regarding trans women athlete participation in female categories, resulting in several banning participation. This review aims to discuss the scientific evidence and provide appropriate guidance for the inclusion of trans women in elite competitive female fencing categories. Fencing is an intermittent sport, where competitions can span 1 to 3 days. The lunge is the most common movement used to attack opponents, where a successful hit relies on the speed of the action. Male puberty induced increased circulating testosterone promotes a greater stature, cardiovascular function, muscle mass, and strength compared to cisgender females, culminating in a ~12-40% sport performance advantage. Elite cisgender male fencers perform significantly higher, ~17-30%, jump heights and leg power measures compared to elite cisgender female fencers, resulting in faster lunges. Trans women receiving androgen-suppression therapy for 12 months showed significant reductions in strength, lean body mass, and muscle surface area, but even after 36 months, the measurements of these three indices remained above those for cisgender females. Previous male muscle mass and strength can be retained through continuation of resistance training. The literature reviewed shows that there is a retained physiological advantage for trans women who have undergone male puberty when participating in the elite competitive female fencing category. A proposed solution of an open or third gender category for elite fencing competition promotes fair competition, while allowing trans women to compete in their chosen sport.